Upaya Mengembangkan Unit Umkm Es Coklatone Mamira Melalui Pelatihan Dan Pendamipingan Digitalisasi Umkm Bersama Pt. Narasumber Teknologi Indonesia - Mustabsyiroh Kumala; Aufa Izzuddin Baihaqi (Universitas Muhammadiyah Manado, 2023)
The development of information technology is so fast, fast, and accurate. Currently, information technology has become the main facility of activity that makes a significant contribution to all sectors of life, which indirectly contributes to business growth. MSME (Micro, Small and Medium Enterprises) in Indonesia is one of the business sectors that is mostly run by business actors. However, one of the challenges for MSMEs is to face digital competition in the business sector so that they can survive in the midst of competition. This study aims to provide information regarding MSME development strategies in utilizing the digital economy. The method used in this activity is to use a quality approach through outreach, implementation and mentoring. The result of this activity is to help digitize the marketing of MSME Es Coklatone Mamira products. So that this activity can help these MSMEs in expanding market share.